Solidity and Professionalization of Translation: Turkey as a Case in Point - Yılmaz-Gümüş, Volga (HERMES - Journal of Language and Communication in Business, 2018)
This study sets out to describe the state of the translation (not interpreting) profession in Turkey, approached by means of indicators based on professionalization (university-based translator training, legal instruments introduced to regulate the market, and professional associations) and solidity of the profession (proportion of men vs. women, translation graduates working as translators, freelance vs. in-house translators, and commitment to the profession). The indicators are investigated by analyzing documents (such as Regulation on the Public Notary, the National Occupational Standards for translators and interpreters, and the Prime Ministry’s report on the translation profession in Turkey), as well as survey and interview data gathered from the graduates of university translation programs, representing freelancers, in-house translators, and language teachers. The increasing number of university-based translation programs, legal instruments and translator associations suggests that continuous attempts have been made to enhance the degree of professionalization in translation. On the other hand, quantitative analyses of a survey administered to translation graduates indicate that the proportion of female translators is overwhelmingly high, that graduates tend to work as freelance translators, but freelancing is mostly not their main role, and that the graduates mostly have a positive perception of training, but do not feel prepared to enter the market after graduation. The findings of document and empirical analyses show that all traits of an established profession are still not present in translation while significant steps have been taken on the way to solidity and professionalization.